2018
DOI: 10.1161/jaha.117.007452
|View full text |Cite
|
Sign up to set email alerts
|

Association of Peripheral Artery Disease With Incident Atrial Fibrillation: The ARIC (Atherosclerosis Risk in Communities) Study

Abstract: BackgroundAlthough peripheral artery disease as defined by ankle‐brachial index (ABI) is associated with incident atrial fibrillation (AF), questions remain about the risk of AF in borderline ABI (>0.90 to <1.0) or noncompressible arteries (>1.4). We evaluated the association of borderline ABI and ABI >1.4 in the ARIC (Atherosclerosis Risk in Communities) study, a population‐based prospective cohort study.Methods and ResultsWe included 14 794 participants (age, 54.2±5.8 years, 55% women, 26% blacks) with ABI m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 28 publications
(50 reference statements)
0
21
0
Order By: Relevance
“…Similar data were retrieved when the meta‐regression analysis was performed according to the ABI classes (data not shown). A cumulative cubic spline model was obtained, pooling together the spline curves from the 3 studies included in the analysis,6, 7, 8 confirming the inverse dose‐effect response between ABI and the risk of incident AF (Figure 1). The pooled cubic spline also confirmed that the risk is still present, despite being lower, in the borderline ABI class (Figure 1).…”
Section: Accumulating Evidence For a New Pathophysiological Paradigmmentioning
confidence: 70%
See 4 more Smart Citations
“…Similar data were retrieved when the meta‐regression analysis was performed according to the ABI classes (data not shown). A cumulative cubic spline model was obtained, pooling together the spline curves from the 3 studies included in the analysis,6, 7, 8 confirming the inverse dose‐effect response between ABI and the risk of incident AF (Figure 1). The pooled cubic spline also confirmed that the risk is still present, despite being lower, in the borderline ABI class (Figure 1).…”
Section: Accumulating Evidence For a New Pathophysiological Paradigmmentioning
confidence: 70%
“…To reach our aim, we performed a meta‐analysis and meta‐regression of data coming from the 3 studies6, 7, 8 (Table), including a total of 26 505 subjects. Bayesian meta‐analyses under heterogeneity were conducted by means of hierarchical (log‐) gaussian models with informative priors, according to previously published articles 10.…”
Section: Accumulating Evidence For a New Pathophysiological Paradigmmentioning
confidence: 99%
See 3 more Smart Citations